2021
DOI: 10.1021/acsaem.1c01713
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Nanoscale Silicon inside Carbon Fiber as Flexible Self-Supporting Anode Material for Lithium-Ion Battery

Abstract: At present, the main limitations for the practical application of silicon (Si) as an anode material of a lithium-ion battery are huge volume variation and low electrical conductivity. Core–shell silicon/carbon (Si/C) composites can greatly relieve the Si large volume change and accelerate the low Li+ conductivity; however, cracking of carbon shell and the failure of the electrode structure still limit the lithium storage capability and cyclic life. Herein, a flexible freestanding N-doped core–shell Si/C nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Besides, while the current density returns to 0.1 A g À1 , the reversible capacity of SMCs can immediately recover to 1881.8 mA h g À1 , suggesting excellent rate capability. A discharge specic capacity of 1035.1 mA h g À1 aer 300 cycles for SMCs electrode at a higher current density of 1.0 A g À1 was attained, which is higher than the values from the most recent reports [6][7][8][9]11,15,[22][23][24] (for detailed data, see Table S1 †). Compared with the third cycle, the capacity retention of the 300th cycle is 46.4%.…”
Section: Resultsmentioning
confidence: 59%
“…Besides, while the current density returns to 0.1 A g À1 , the reversible capacity of SMCs can immediately recover to 1881.8 mA h g À1 , suggesting excellent rate capability. A discharge specic capacity of 1035.1 mA h g À1 aer 300 cycles for SMCs electrode at a higher current density of 1.0 A g À1 was attained, which is higher than the values from the most recent reports [6][7][8][9]11,15,[22][23][24] (for detailed data, see Table S1 †). Compared with the third cycle, the capacity retention of the 300th cycle is 46.4%.…”
Section: Resultsmentioning
confidence: 59%
“…Li et al showed that after the carbonization of polyacrylonitrile (PAN), it was doped with nitrogen atoms and exhibited excellent chemisorption for Li + . Experiments verified that the initial specific discharge capacity of the battery was 1441 mAh g –1 , the capacity retention rate at 0.5 C was 76.9%, and the capacity decay rate per cycle was only 0.1% . Our group prepared a N-doped hierarchically porous membrane electrode with CNTs and PAN that was used as a diaphragm to assemble lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 89%
“…Experiments verified that the initial specific discharge capacity of the battery was 1441 mAh g −1 , the capacity retention rate at 0.5 C was 76.9%, and the capacity decay rate per cycle was only 0.1%. 21 Our group prepared a Ndoped hierarchically porous membrane electrode with CNTs and PAN that was used as a diaphragm to assemble lithium-ion batteries. In our previous work, the application of the membrane electrode, without any modification, as an interlayer on the lithium sheet played a role in redistributing the Li + flux and inducing uniform deposition on the Li plate, thus inhibiting the growth of lithium dendrites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…), which are electrochemically silent and become a liability in the form of additional unwanted weight, resulting in much reduced overall specic capacity. [41][42][43][44][45] These silicon oxycarbide (SiC x O 4Àx ) black glasses (BG) consist of mixed structural units of SiC 4 , SiC 3 O, SiC 2 O 2 , SiCO 3 , and SiO 4 arranged in amorphous fashion. 36,39,40 In addition, the inherent free carbon domain can also be present in this amorphous network.…”
Section: Materials Designmentioning
confidence: 99%